Religiosity and Prosocial Behavior on Student of Islamic and Public Schools at Banda Aceh, Indonesia - Safrilsyah, Safrilsyah; Mohd. Yusoff, Mohd. Zailani; Othman, Mohamad Khairi; Ibrahim, Ibrahim (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to examine religiosity's relationship with prosocial students' behavior in Aceh, Indonesia. This research was a quantitative survey using cross-sectional studies and data collected from selected individuals over a specific period. The researchers collected data from 649 students (299 male and 350 females) using a non-proportional stratified sampling. Data were collected using two questionnaires, (1) Islamic Religiosity by using SPPIM-R and (2) Prosocial Behavior by using PTM-R. The data were analyzed descriptively. The statistical analysis (hypothesis testing) was done using product-moment correlation assisted by SPSS/PC Ver.16.00. The result showed that there was a significant positive correlation between religiosity and prosocial behavior among students. The respective R-square was 0.494, and the result of the coefficient was 0.703. However, there was no significant difference in prosocial behavior among religious high school and public school students, although female students were more prosocial than male students.